PENGARUH AROMATERAPI LEMON TERHADAP INSOMNIA IBU PERIMENOPAUSE DI RT 34 RW 12 KELURAHAN II ILIR PALEMBANG - Purwani, Rani; Apriyani, Titin; Fatrin, Tiara (STIKES Abdurahman. Pusat Informasi dan Manajemen, 2025)
Insomnia is the inability to get enough sleep, both quality and quantity. Sleep disorders that occur include inappropriate sleep length or sleep quantity and sleep quality such as ineffective sleep. One effort to overcome insomnia is with aromatherapy therapy. The essential content of lemon is to stabilize the central nervous system, thereby producing a calming effect and overcoming insomnia. This research aims to determine the effect of lemon aromatherapy on isomnia in perimenopausal mothers. This type of research is quantitative with a Quasi Experimental design with a One Group Preetest Posttest design. The population of this study were all perimenopause mothers in RT 34 RW 12 Kelurahan II Ilir. The sample in this study was 15 respondents, who were made into 1 group, namely, the intervention group. where the intervention group was the group that was given lemon aromatherapy for 7 days for 10 minutes, as many as 15 respondents. The analysis used was the Wilcoxon. The results of this study showed the effect of lemon aromatherapy in overcoming insomnia in perimenopausal mothers, a p-value of 0.001 was obtained. Where the significance value is smaller than the α value of 0.05. The conclusion of this study is that Ho is rejected, meaning that there is a significant effect in overcoming insomnia in the intervention group.